Study on the influence mechanism of digital economy on agricultural carbon emission reduction-based on the perspective of fertilizer saving and efficiency improvement - Yang, He; Wen, Tiejun (Frontiers in Sustainable Food Systems, 2025)
Agricultural carbon emissions is one of the most important part of global greenhouse gasses, its governance is an significant action to deal with climate change and achieve SDG13. This study takes China, a large agricultural country, as an example. Using China’s provincial panel data from 2011 to 2021, the study empirically examines the relationship between the digital economy and agricultural carbon emissions, as well as its characteristic fact through a two-way fixed-effects model. It also explores the intrinsic mechanism of the two key variables from the perspective of government finance through the model of moderating effects. The conclusions indicate that: the increase of the level of digital economy within the station has a notable inhibitory effect on the agricultural carbon emissions; in terms of the temporal effect, the inhibition of the digital economy on the agricultural carbon emissions is not only reflected in the current period, but also in the next two periods; In relation to the spatial heterogeneity, the effect of carbon emission reduction in the agricultural field shows the following characteristics spatial distribution, the reduction effect presents the spatial distribution characteristics of “west > east, central is not obvious,” “the north is significant, the south is vice versa”; As for influence mechanism, the government’s financial support in environmental protection and financial support in the field of science and technology positively catalyzes the suppression effect of the digital economy on the agricultural carbon emissions. The mechanism of influence, There is an intermediary way to reduce the use of agricultural chemical fertilizers and increase the yield of agricultural products in the inhibitory effect of digital economy on agricultural carbon emissions. in addition, the government’s financial support in environmental protection and financial support in the field of science and technology have positively catalyzed the carbon reduction effect of digital economy in the field of agriculture, which provides empirical evidence for exploring the carbon reduction path of agricultural digital transformation and the synergistic effect of “policy technology” in sustainable agricultural development.